2007
DOI: 10.1371/journal.pone.0000762
|View full text |Cite
|
Sign up to set email alerts
|

Homosexual Women Have Less Grey Matter in Perirhinal Cortex than Heterosexual Women

Abstract: Is sexual orientation associated with structural differences in the brain? To address this question, 80 homosexual and heterosexual men and women (16 homosexual men and 15 homosexual women) underwent structural MRI. We used voxel-based morphometry to test for differences in grey matter concentration associated with gender and sexual orientation. Compared with heterosexual women, homosexual women displayed less grey matter bilaterally in the temporo-basal cortex, ventral cerebellum, and left ventral premotor co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 37 publications
(41 reference statements)
3
30
0
1
Order By: Relevance
“…Given this unequal distribution and given that information on sexual orientation was unavailable for control subjects, we abstained from conducting analyses for different subtypes. However, a number of previous findings appear to indicate brain-structural alterations associated with sexual orientation (Allen and Gorski, 1992; Byne et al, 2001; LeVay, 1991; Ponseti et al, 2007; Savic and Lindstrom, 2008; Swaab and Hofman, 1990; Witelson et al, 2008). Moreover, a highly controversial line of research has suggested that homosexual and non-homosexual MTF transsexualism are etiologically heterogeneous (Blanchard, 1989a; Blanchard, 1989b), which may be associated with differences in neuroanatomy.…”
Section: Discussionmentioning
confidence: 98%
“…Given this unequal distribution and given that information on sexual orientation was unavailable for control subjects, we abstained from conducting analyses for different subtypes. However, a number of previous findings appear to indicate brain-structural alterations associated with sexual orientation (Allen and Gorski, 1992; Byne et al, 2001; LeVay, 1991; Ponseti et al, 2007; Savic and Lindstrom, 2008; Swaab and Hofman, 1990; Witelson et al, 2008). Moreover, a highly controversial line of research has suggested that homosexual and non-homosexual MTF transsexualism are etiologically heterogeneous (Blanchard, 1989a; Blanchard, 1989b), which may be associated with differences in neuroanatomy.…”
Section: Discussionmentioning
confidence: 98%
“…The corresponding cluster of convergent activity also comprised the left perirhinal cortex. Interestingly, gray matter of this region displays a more male-like structural pattern in homosexual women (Ponseti et al, 2007). Together, these findings can be interpreted as support for sex-atypical prenatal androgenization in homosexual women and for early determination of sexual preference in the fetal stage on the basis of hormonal influence in general.…”
Section: Discussionmentioning
confidence: 99%
“…VBM of T1-weighted MRI images has identified areas in the brain where regional grey matter volume is correlated with individual variations in genotype (Binkofski et al, 2007;Pezawas et al, 2004), motor skills (Gaser and Schlaug, 2003), topographical memory (Maguire et al, 2003), or sexual orientation (Ponseti et al, 2007).…”
Section: Introductionmentioning
confidence: 99%